2021
DOI: 10.1186/s13018-021-02449-8
|View full text |Cite
|
Sign up to set email alerts
|

A technique for repairing rotator cuff transtendinous tears with a remnant attached to the footprint

Abstract: Background Some unusual rotator cuff (RC) tears are located in more proximal tendinous portions, with substantial remnant tissue attached to the footprint. The two options for surgical repair are sacrificing or preserving the remnant tissue. We introduce a surgical repair technique that preserves as much of the remnant footprint as possible. Surgical technique A double-loaded suture anchor is inserted into the subchondral bone at the medial portion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…In contrast, several studies found that the native enthesis was well preserved in 75% of acute rotator cuff tear cases. 3 , 26 , 33 Therefore, we believe that the RP-BMS technique may be more appropriate for the repair of acute rotator cuff tears than the conventional repair technique. This technique may improve tendon integrity of repair by preserving the remnant tissue of the torn tendon in acute rotator cuff tear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, several studies found that the native enthesis was well preserved in 75% of acute rotator cuff tear cases. 3 , 26 , 33 Therefore, we believe that the RP-BMS technique may be more appropriate for the repair of acute rotator cuff tears than the conventional repair technique. This technique may improve tendon integrity of repair by preserving the remnant tissue of the torn tendon in acute rotator cuff tear.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 8 , 31 Therefore, we have reason to believe that a modified surgical technique that utilizes the native enthesis of the rotator cuff by preserving the rotator cuff remnant tissue may stimulate the inherent healing potential of the rotator cuff tendon-bone interface. 3 , 28 …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of aging on the rotator cuff have previously been studied mainly at the tendon-to-bone interface 34,35 . However, most tears are found in tendon tissues that are proximal to the enthesis, instead of at the enthesis itself 28 . The histological analysis in the present study revealed that tendon tissues proximal to the enthesis site exhibited more severe degenerative changes.…”
mentioning
confidence: 99%